(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Burn injuries represent a significant & often devastating public health concern in India. The burden of burns is notably higher among women & children due to domestic accidents, including cylinder/stove burns and scalds. Aims & objectives: To establish a detailed clinico-epidemiological profile of burn patients admitted to a tertiary care hos pital, including demographics, burn severity, causes and treatment outcomes. Materials & Methods: This retrospective study was conducted over a one-year period, at Uttar Pradesh University of Medical Sciences in Saifai, Etawah, UP, India. The data retrieval process involved the examination of medical records and documents contained within the patient’s hospital records. Results: Total 323 patients were analyzed. Out of them, 56.9% were male and 43.1% were female. Most were under 10 years (94), followed by 21-30 years (69). Flame burns were the most common (48.3%), followed by scalds (27.6%), electrical burns (23.8%), and chemical burns (0.3%). Winter saw the highest incidence (40.8%). Accidental burns accounted for 77.1%, with 19.8% of patients dying, mainly due to septicemia (13.3%). Mortality increased with burn severity: 3.6% died with less than 30% TBSA, 36.2% with 31-60% TBSA, and 65.7% with over 60% TBSA. Most burns affected the right upper limb (64.4%). Conclusion: A developing country like India requires an extensive public education program to raise awareness about the various causes of burns and effective prevention methods. Additionally, there is a need for burn care hospitals that are both accessible and affordable to the general population.